Hyperpolarization-Activated Cyclic Nucleotide-Gated Ion (HCN) Channels Regulate PC12 Cell Differentiation Toward Sympathetic Neuron - Zhong, Li-Ying; Fan, Xin-Rong; Shi, Zhang-Jing; Fan, Zhong-Cai; Luo, Jian; Lin, Na; Liu, Ying-Cai; Wu, Lin; Zeng, Xiao-Rong; Cao, Ji-Min; Wei, Yan (Frontiers in Cellular Neuroscience, 2019)
Hyperpolarization-activated cyclic nucleotide-gated ion channels (HCN channels) are widely expressed in the central and peripheral nervous systems and organs, while their functions are not well elucidated especially in the sympathetic nerve. The present study aimed to investigate the roles of HCN channel isoforms in the differentiation of sympathetic neurons using PC12 cell as a model. PC12 cells derived from rat pheochromocytoma were cultured and induced by nerve growth factor (NGF) (25 ng/ml) to differentiate to sympathetic neuron-like cells. Sympathetic directional differentiation of PC12 cells were evaluated by expressions of growth-associated protein 43 (GAP-43) (a growth cone marker), tyrosine hydroxylase (TH) (a sympathetic neuron marker) and neurite outgrowth. Results show that the HCN channel isoforms (HCN1-4) were all expressed in PC12 cells; blocking HCN channels with ivabradine suppressed NGF-induced GAP-43 expression and neurite outgrowth; silencing the expression of HCN2 and HCN4 using siRNA, rather than HCN1 and HCN3, restrained GAP-43 expression and neurite outgrowth, while overexpression of HCN2 and HCN4 channels with gene transfer promoted GAP-43 expression and neurite outgrowth. Patch clamp experiments show that PC12 cells exhibited resting potentials (RP) of about 65 mV  70 mV, and also presented inward HCN channel currents and outward (K+) currents, but no inward voltage-gated Na+ current was induced; NGF did not significantly affect the RP but promoted the establishment of excitability as indicated by the increased ability to depolarize and repolarize in the evoked suspicious action potentials (AP). We conclude that HCN2 and HCN4 channel isoforms, but not HCN1 and HCN3, promote the differentiation of PC12 cells towards sympathetic neurons. NGF potentiates the establishment of excitability during PC12 cell differentiation.